State feedback stabilization of discrete linear switching systems subject to nonsymmetrical state and control bounds - Liu, Zhiyuan; Fan, Guowei; Chen, Hong (Journal of control theory and applications, 2012)
Stabilization problem of discrete-time linear switching systems with bounds on the state and control input is solved in this paper. First, the synthesis of state feedback controllers that ensure the stability of closed-loop switching systems is studied under a sufficient condition. By using the idea of positive invariance, a stabilizing controller design methodology is proposed. Based on these results, the convergence rate problem is also discussed. A state feedback controller that guarantees the optimal convergence rate of closed-loop switching systems is obtained via optimization. Finally, an example made up of two subsystems is studied to show the application of our method.